The role of sports activities in developing citizenship for students of sport sciences, University of Kirkuk - Mohammed Qasim Mohammed; Maan Hasan Mahmood; Moatasem Azeez Kahlid; Maad Abed Ibrahim (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: Sports enhance cognitive abilities of individual level.